High-efficiency removal of dyes from wastewater by fully recycling litchi peel biochar. (May 2020) - Wu, Jia; Yang, Jianwei; Feng, Pu; Huang, Guohuan; Xu, Chuanhui; Lin, Baofeng
Abstract: Litchi peel biochar was prepared by hydrothermal carbonization and subsequent activation process, and its adsorption on congo red and malachite green were investigated. The structural characteristics and adsorption properties of litchi peel biochar were studied by Scanning electron microscopy, X-ray diffractometer, Brunauer-Emmett-Teller, and dye adsorption experiments, and the adsorption mechanism between litchi peel biochar and dye molecules was analyzed by X-ray photoelectron spectroscopy and Fourier transform infrared spectroscopy. The results showed that the litchi peel biochar had a high specific surface area and pore volume of 1006 m 2  g −1 and 0.588 cm 3  g −1, respectively, and its adsorption capacity for congo red and malachite green was 404.4 and 2468 mg g −1, respectively. The excellent adsorption properties were due to hydrogen bonding, π-π interaction, pore filling and electrostatic interactions. In addition, the reactivated litchi peel biochar also showed good adsorption performance, and all the adsorbed dyes were completely removed by reactivation, which realized complete recycling of the litchi peel biochar without causing secondary environmental pollution. Therefore, litchi peel biochar was expected to be an effective and recyclable adsorbent for removing congo red and malachite green from aqueous solutions. Graphical abstract: Image 1 Highlights: Litchi peel biochar adsorbent was prepared by simple hydrothermal treatment. The biosorbent had high adsorption performance for congo red and malachite green. The adsorption might be involved with H-bond, pore filling and electrostatic effect. After re-activation of HLP850, the adsorbed dye was completely removed.